2018
DOI: 10.3390/en11020299
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel from Hydrolyzed Waste Cooking Oil Using a S-ZrO2/SBA-15 Super Acid Catalyst under Sub-Critical Conditions

Abstract: Due to rapid changes in food habits, a substantial amount of waste fat and used oils are generated each year. Due to strong policies, the disposal of this material into nearby sewers causes ecological and environmental problems in many parts of the world. For efficient management, waste cooking oil, a less expensive, alternative and promising feedstock, can be used as a raw material for producing biofuel. In the present study, we produced a biodiesel from hydrolyzed waste cooking oil with a subcritical methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
(15 reference statements)
0
23
0
Order By: Relevance
“…The SBA-15 support and the S-TiO2/SBA-15 catalyst both exhibited XRD diffraction patterns with one very intense diffraction peak and two small peaks. The intense peak was indexed as d100, and the smaller peaks were indexed as d110 and d200, which are characteristic of the 2-D hexagonal (p6 mm) ordered mesoporous structure of the SBA-15 with excellent textural uniformity [2]. From this finding, it can be concluded that the S-TiO2/SBA-15 catalyst retains the mesoporous structure of the SBA-15 support.…”
Section: Physical Properties Of the Catalystmentioning
confidence: 85%
See 4 more Smart Citations
“…The SBA-15 support and the S-TiO2/SBA-15 catalyst both exhibited XRD diffraction patterns with one very intense diffraction peak and two small peaks. The intense peak was indexed as d100, and the smaller peaks were indexed as d110 and d200, which are characteristic of the 2-D hexagonal (p6 mm) ordered mesoporous structure of the SBA-15 with excellent textural uniformity [2]. From this finding, it can be concluded that the S-TiO2/SBA-15 catalyst retains the mesoporous structure of the SBA-15 support.…”
Section: Physical Properties Of the Catalystmentioning
confidence: 85%
“…The decrease in the surface area, pore volume, and pore size are due to the gradual accumulation of the metal oxide species blocking some of the pores of the support during preparation. However, the decrease in the surface area is very small, suggesting that the active sulfated metal oxide species are highly dispersed on the surface of the support [2,4]. Figure 3 shows the XRD patterns of the support and catalyst as measured using an X-ray diffractometer system (D/MAX-2500V).…”
Section: Physical Properties Of the Catalystmentioning
confidence: 99%
See 3 more Smart Citations